Effect of Consultation Number on the Assessment and Treatment of Polycystic Ovary Syndrome - Wang Y; Chen J; Dong H; Ma RL; Zou Y; Wang W; Zheng Q; Feng Y; Tan Z; Zeng X; Zhao Y; Deng Y; et al. (International Journal of Women's Health, 2024)
Yue Wang,1 Jie Chen,1 Han Dong,2 Rui-Lin Ma,1 Ying Zou,3 Wei Wang,4 Qingmei Zheng,5 Ying Feng,6 Zhangyun Tan,7 Xiaoqin Zeng,8 Yinqing Zhao,7 Yan Deng,1 Yanfang Wang,1 Bei Gu,9 Aijun Sun1,10 1National Clinical Research Center for Obstetric & Gynecologic Diseases Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100730, People’s Republic of China; 2Department of Obstetrics and Gynecology, Women and Children’s Hospital of Jinzhou, Jinzhou, Liaoning, 121000, People’s Republic of China; 3Department of Obstetrics and Gynecology, Hunan Provincial Maternal and Child Health Care Hospital, Changsha, Hunan, 410008, People’s Republic of China; 4Department of Reproductive Medicine, the Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People’s Republic of China; 5Department of Gynecology, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, 266500, People’s Republic of China; 6Department of Obstetrics and Gynecology, the Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China; 7Department of Obstetrics and Gynecology, Xinhui Maternity and Children’s Hospital, Nanning, Guangxi, 529100, People’s Republic of China; 8Department of Gynecology, Guangzhou Women and Children’s Medical Center, Guangzhou, Guangdong, 510000, People’s Republic of China; 9Department of Obstetrics and Gynecology, Beijing Shijitan Hospital, Capital Medical University, Peking University Ninth School of Clinical Medicine, Beijing, 100038, People’s Republic of China; 10Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Beijing, 100010, People’s Republic of ChinaCorrespondence: Aijun Sun, Email saj@pumch.cnBackground: The basic medical education stage is not enough to support physicians to fully diagnose and evaluate polycystic ovary syndrome (PCOS). The study aims to discover the difference in treatment choice between participants with different annual consultation number of PCOS, to promote lifelong learning, and drive balanced development within healthcare.Methods: This is a multicenter cross-sectional survey. Participants’ basic information, knowledge of PCOS and treatment options were collected online. According to the annual consultation number of patients with PCOS, physicians were divided into three groups: 0– 50 people/yr, 50– 200 people/yr, and > 200 people/yr, and the results were derived from χ2 test, Fisher exact test, and multivariate logistic regression analysis.Results: The study analyzed 1689 questionnaires, and 1206 physicians (71.4%) received less than 50 women per year, 388 physicians (30.0%) with an annual number of 50– 200 women, and 95 physicians (5.6%) with patient turnover for more than 200 people. Reproductive endocrinologists generally have higher access to the clinic. As the number of visits increases, more and more physicians would perceive patients as more likely to have abnormal blood glucose and heavy weight. Physicians with large numbers of consultations are more likely to use Asian or Chinese standards to assess obesity. The multivariate analysis involved variables such as age, hospital level, specialty, and patient turnover annually, and more young doctors actively assessed lipid profile (odds ratio (OR) 1.56, 95% confidence interval (CI) (1.16, 2.16)), and primary hospitals (OR 0.65 CI (0.44, 0.89)) chose OGTT for blood glucose assessment less than tertiary hospitals. Physicians in secondary hospitals are more aggressive in evaluating androgens.Conclusion: Our survey found differences in endocrine assessment, metabolic screening, and treatment in PCOS women in terms of the number of obstetrician-gynecologists who received different patient consultation numbers. The importance of continuing education for physicians is emphasized, to promote lifelong learning.Keywords: polycystic ovary syndrome, consultation number, lifelong learning, insulin resistance, obesity, hyperandrogenemia, metformin